2020
DOI: 10.3390/ijerph17176381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fecal Coliform Prevalence and Physicochemical Indicators in the Effluent from a Wastewater Treatment Plant in the North-West Province, South Africa

Abstract: Compliance of the effluents from wastewater treatment plants (WWTPs) to the regulatory standards, which mostly entail the removal/reduction of organic waste and deactivation of the potential microbial pathogens is of great importance. The detection of indicator parameters can be used to determine the effectiveness of a WWTP and the level of compliance with the South African regulatory standards. The performance of the WWTP was assessed by biological, physical and chemical measures in wastewater final effluent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…However, faulty clarifiers, sludge reticulation due to aerator breakdown and stabilization ponds that are not associated with disinfection have been identified during sampling regime with high Vibrio densities. These observations were consistent with the findings of [47] that reported polluted effluents in their study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, faulty clarifiers, sludge reticulation due to aerator breakdown and stabilization ponds that are not associated with disinfection have been identified during sampling regime with high Vibrio densities. These observations were consistent with the findings of [47] that reported polluted effluents in their study.…”
Section: Discussionsupporting
confidence: 93%
“…Most South African wastewater treatment works disinfect wastewater by chlorination prior to discharge into receiving watersheds [47]. The goal is to remove pathogens from wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…The plant of interest in this study is situated in the North West Province of South Africa. The town where the plant is situated has a population of approximately 124 000 inhibitants and is an industrial and agricultural growth point (Makuwa et al, 2020). The plant therefore receives municipal domestic sewage and wastewater that is heavily influenced by household and industrial water use.…”
Section: Study Areamentioning
confidence: 99%
“…Numerical simulations and experimental research are both effective strategies for studying WWTPs. At present, experimental studies on sewage treatment are mostly done on the structural transformation and process upgrades of WWTPs [34]. For example, Cao et al [35] applied an improved four-stage segmented process to treat low C/N urban sewage, and they found that the flow distribution ratio of the four-stage A/O was 20:35:35:10.…”
Section: Introductionmentioning
confidence: 99%